Uji Aktivitas Antioksidan Kombucha Bunga Telang (Clitoria ternatea) sebagai Upaya Pencegahan Penyakit Diabetes Melitus (DM) - Dita Apriana Dwi Astuti; Aprilia Anjarwati; Saiful Muttaqin (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes mellitus (DM) is a chronic disease with a high prevalence, including in Indonesia (10.6%), and leads to serious complications due to endothelial cell damage and oxidative stress. Synthetic drugs often have side effects, thus there is a need for safe and effective herbal alternatives. This study aims to evaluate the antidiabetic potential and antioxidant activity of kombucha formulated with butterfly pea flowers (Clitoria ternatea) as a natural therapy based on probiotics and bioactive compounds from local plants. The butterfly pea kombucha was fermented for 12 days, and its total flavonoid content and antioxidant activity were analyzed using spectrophotometry. The kombucha extract at a concentration of 0.0216% b/v showed strong antioxidant activity, with an IC50 value of 27.80 ppm and an inhibition percentage that increased from 14.72% at a concentration of 5 ppm to 20.23% at 1 ppm. The standard curve showed a linear equation of y = 1.335x + 12.897 with a coefficient of determination R² = 0.9353.